Do linear molecules always dissociate along their axis? Intra-molecular scattering within Diiodoacetylene. (July 2015) - De, Sankar; Tezuka, H; Bhatt, P; Vesapidze, G; Safvan, C P; Matsumoto, J; Shiromaru, H
Synopsis: We present here the coincidence study of multiply charged, dissociative diiodoacetylene. We find that instead of breaking up along the molecular axis as in the case of acetylene, the carbon ions of highly charged diiodoacetylene molecule tends to dissociate perpendicularly with respect to the iodine ones. This feature carries a strong signature of intra-molecular scattering between its breakup partners. The heavier iodines block the path of carbons and give rise to 'doughnut' - shaped momentum islands.